2018
DOI: 10.1017/thg.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes of Twins Compared With Singleton Children: A Systematic Review

Abstract: More than 200 million children aged <5 years fail to reach their full cognitive potential, and children born as twins are particularly at risk. In this article, we review studies that examined differences in the neurodevelopmental outcomes of twins compared to singletons. We searched the Medline database for articles on twins, singletons, neuro, and cognitive development. We also inspected bibliographies of relevant publications to identify related articles from 2011 to 2017. Our search criteria yielded 162 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…There is limited literature on the outcomes in periviable births regarding differences in between multiples and singletons which warrants further investigation. 14 Our study demonstrated that self-reported maternal Black race was associated with increased risk for g-tube placement in periviable infants that survived to discharge, a finding that has not been previously reported in literature. The composite outcome of death or g-tube placement was not significant.…”
Section: Discussionsupporting
confidence: 44%
“…There is limited literature on the outcomes in periviable births regarding differences in between multiples and singletons which warrants further investigation. 14 Our study demonstrated that self-reported maternal Black race was associated with increased risk for g-tube placement in periviable infants that survived to discharge, a finding that has not been previously reported in literature. The composite outcome of death or g-tube placement was not significant.…”
Section: Discussionsupporting
confidence: 44%
“…Within this framework, twin gestation has been traditionally associated with an increased risk of perinatal mortality and morbidity ( 15 , 16 ). Moreover, it has been suggested that twins are at greater risk of adverse long-term neurodevelopmental outcomes than singletons, but the evidence is inconsistent ( 17 ). Moreover, longitudinal studies examining the neurodevelopmental outcomes among preterm twins and higher-order multiples are limited, and few of those studies had long follow-up durations.…”
Section: Introductionmentioning
confidence: 99%
“…29,32 Nevertheless, when evaluating early child neurodevelopment, few or no significant differences in sequelae have been found between preterm-born multiples and singletons. [33][34][35] While there are many antenatal and intrapartum factors impacting twin gestations, zygosity and birth order are the two core factors for consideration when examining childhood sequelae. Zygosity is used to evaluate heritability, commonly determined by the concordance of outcomes.…”
Section: Introductionmentioning
confidence: 99%